Development of 2-deoxystreptamine–nucleobase conjugates for the inhibition of oncogenic miRNA production. Issue 3 (18th January 2022) - Tran, Thi Phuong Anh; Poulet, Sylvain; Pernak, Mélanie; Rayar, Anita; Azoulay, Stéphane; Di Giorgio, Audrey; Duca, Maria
Abstract : 2-deoxystreptamine (2-DOS) conjugates with artificial nucleobases were designed and synthesized to inhibit pre-miR-372 processing into oncogenic miRNA and were discovered to be promising inhibitors when compared to their neomycin counterpart. Abstract : The discovery of new original scaffolds for selective RNA targeting is one of the main challenges of current medicinal chemistry since therapeutically relevant RNAs represent potential targets for a number of pathologies. Recent efforts have been devoted to the search for RNA ligands targeting the biogenesis of oncogenic miRNAs whose overexpression has been directly linked to the development of various cancers. In this work, we developed a new series of RNA ligands for the targeting of oncogenic miRNA biogenesis based on the 2-deoxystreptamine scaffold. The latter is part of the aminoglycoside neomycin and is known to play an essential role in the RNA interaction of this class of RNA binders. 2-deoxystreptamine was thus conjugated to natural and artificial nucleobases to obtain new binders of the oncogenic miR-372 precursor (pre-miR-372). We identified some conjugates exhibiting a similar biological activity to previously synthesized neomycin analogs and studied their mode of binding with the target pre-miR-372.